Assessment of Indoor and Outdoor Air Pollution in an Oil-Producing Nigerian Community: Evidence from Ozoro General Hospital, Delta State, Nigeria - Obaro Oghenejabor; Benjamin Evi Idisi; Abdullahi Mustapha (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2026)
This study assessed the physicochemical and microbial characteristics of indoor and outdoor air quality at Ozoro General Hospital, situated within Nigeria’s oil-producing Niger Delta region. The aim was to evaluate pollutant levels, compare them with international standards, and determine the influence of indoor versus outdoor sources on hospital environments. Air sampling was conducted at three indoor sites (Card Room, Waiting Room, Consultant Office) and one outdoor control point using portable air quality monitors and passive microbial culture techniques. Results showed that PM₂.₅ levels in the Consultant Office (8.67 µg/m³) exceeded WHO’s 5 µg/m³ guideline, while bacterial (2012.65 CFU/m³) and fungal (1065.26 CFU/m³) loads were highest in the Waiting Room. Indoor/outdoor ratios confirmed stronger indoor contributions linked to occupancy and poor ventilation. It is recommended that stricter environmental controls on gas flaring be enforced and hospital-level interventions, such as improved ventilation and hygiene practices, be adopted to safeguard public health.